Modified Palliation in Cancer Patients during COVID-19 Pandemic - Wagle, Bhawna; Koirala, Eliza (Nepalese Journal of Cancer, 2020)
Corona virus disease 2019 (COVID 19) has put huge challenge to the health delivery system all across the globe. The risk of mortality due to COVID 19 is highest on critically ill patients and those with preexisting disease. Palliative and end of life care are no exceptions to the surge in increased demand for health care services. It is now an essential part of global health care. The benefits of early palliative care are already well established. In the pandemic like this, we must not pull back the services, particularly in these vulnerable groups. It is important to determine how best to deliver palliative care during this crisis. It may include preparedness to shift the focus of resources to community level and the innovative use of telemedicine. Use of telemedicine is to ease patients and minimize caregiver distress, and to prevent hospitalizations. The fear of contracting COVID-19 and the emotional burden during diagnosis requires the need of continuous psychosocial support. These challenges should be handled by specialized and skilled interdisciplinary palliative care team.